Development of an SSI-Based Chemistry E-Module Integrating Islamic Values to Support Critical Thinking in Chemistry Learning - Mimi Herman; Dwivelia Aftika Sari; Ajis Kurniawan; Anisa Anisa; Elvy Rahmi Mawarnis; Hidayat Herman; Akrajas Ali Umar; Muhd Ibrahim (Jurnal Tadris Kimiya, 2026)
Critical thinking skills are essential competencies in 21st-century education; however, preliminary observations indicate that first-semester Chemistry Education students at UIN Mahmud Yunus Batusangkar tend to have limited critical thinking abilities and focus mainly on theoretical understanding. This study aimed to develop a socio-scientific issues (SSI)–based chemistry e-module integrated with Islamic values and to evaluate its feasibility in terms of validity and practicality. A research and development (R&D) approach using the 4D model (Define, Design, Develop, and Disseminate) was employed, with data collected through expert validation instruments and student response questionnaires involving 12 first-semester students. The results showed that the developed e-module achieved a very high level of validity, with an overall mean score of 3.76. In addition, the practicality assessment yielded an average score of 3.39 on a four-point scale, categorized as practical. These findings indicate that the e-module is feasible for use in chemistry learning. The extent to which this e-module supports students' critical thinking skills has not yet been measured and remains a direction for future research, particularly through effectiveness testing in broader instructional settings.